2020
DOI: 10.1021/acs.joc.0c02078
|View full text |Cite
|
Sign up to set email alerts
|

Iodine/DMSO-Promoted Selective Direct Arylthiation of Anilines with Thiols under Metal-Free Conditions

Abstract: An iodine-promoted divergent thiolation of unprotected anilines with thiols for the synthesis of sulfide anilines has been described. The combinational use of I 2 and DMSO played an important role to realize this kind of transformation without the aid of a metal catalyst and strong oxidants. The reaction selectivity was well controlled to provide mono-, bis-, and trisubstituted diaryl sulfide derivatives. More importantly, iodination and sulfenylation can occur simultaneously to provide useful multifunctionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 81 publications
0
10
0
1
Order By: Relevance
“…Although Fu and co-workers showed that uncatalysed thioarylation of unprotected anilines with N -(arylthio)succinimides could be achieved using high temperatures (100 °C) and extended reaction times (21–30 h), 23 examples of catalysed methods with activated N -thiolation reagents are relatively rare and require the use of protected derivatives. 22 a ,24,25 Preliminary work in our group demonstrated that iron-catalysed thioarylation of unprotected anilines gave a mixture of thiolated products via reaction with either the arene or amine moiety. For this reason, N -benzoyl protected p -toluidine 1a was chosen as the model substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Although Fu and co-workers showed that uncatalysed thioarylation of unprotected anilines with N -(arylthio)succinimides could be achieved using high temperatures (100 °C) and extended reaction times (21–30 h), 23 examples of catalysed methods with activated N -thiolation reagents are relatively rare and require the use of protected derivatives. 22 a ,24,25 Preliminary work in our group demonstrated that iron-catalysed thioarylation of unprotected anilines gave a mixture of thiolated products via reaction with either the arene or amine moiety. For this reason, N -benzoyl protected p -toluidine 1a was chosen as the model substrate.…”
Section: Resultsmentioning
confidence: 99%
“…24 In 2021, Zhao et al reported that anilines can actively participate in the synthesis of mono-, bis-, and tri-substituted diaryl sulfides following an effective CDC strategy of aromatic C(sp 2 )−H bonds under metal-free conditions. 25 Interestingly, in the case of arylhydrazines (Ar−NH−NH 2 ), this sulfenylation/selenylation takes place through the elimination of the free diamine moiety (−NH−NH 2 ) as nitrogen (Scheme 1a− c). 23,26 Under this circumstance, exploration of an alternate route for sulfenylation and selenylation of aryl hydrazines where the hydrazine functionality or its congeners remain intact should be considerably important to the synthetic and pharmaceutical chemists.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Incidentally, several notable synthetic approaches including photoredox-catalyzed, transition-metal-catalyzed or metal-free cross-coupling of thiols/thiol surrogates/elemental sulfur or disulfides/diselenides with a variety of aryl halides, aryl diazonium salts, arylmagnesium/arylzinc/arylboronic acid derivatives, and arylhydrazines are frequently used for the synthesis of diverse unsymmetrical diaryl sulfide and selenide compounds. , In recent times, direct oxidative cross-dehydrogenative coupling (CDC) of readily available electron-rich aromatic C­(sp 2 )–H bonds with a variety of thiols/dithiols/diselenides emerges as an attractive environmentally benign synthetic strategy to generate diverse C­(sp 2 )–S/C­(sp 2 )–Se bonds . In 2021, Zhao et al reported that anilines can actively participate in the synthesis of mono-, bis-, and tri-substituted diaryl sulfides following an effective CDC strategy of aromatic C­(sp 2 )–H bonds under metal-free conditions . Interestingly, in the case of arylhydrazines (Ar–NH–NH 2 ), this sulfenylation/selenylation takes place through the elimination of the free diamine moiety (−NH–NH 2 ) as nitrogen (Scheme a–c). , Under this circumstance, exploration of an alternate route for sulfenylation and selenylation of aryl hydrazines where the hydrazine functionality or its congeners remain intact should be considerably important to the synthetic and pharmaceutical chemists.…”
Section: Introductionmentioning
confidence: 99%
“…C–H sulfenylation with various sulfur reagents under transition metal-catalyzed and transition metal-free conditions has received considerable attention. Despite their use, multiple-step procedures are required to create these important moieties. …”
Section: Introductionmentioning
confidence: 99%